Transcription Factor LjWRKY50 Affects Jasmonate-Regulated Floral Bud Duration in Lonicera japonica - Yanfei Li; Yutong Gan; Guihong Qi; Wenjie Xu; Tianyi Xin; Yuanhao Huang; Lianguo Fu; Lijun Hao; Qian Lou; Xiao Fu; Xiangyun Wei; Lijun Liu; et al. (Plants)
Lonicera japonica Thunb. is a traditional Chinese medicinal herb whose floral buds are the primary source of pharmacological compounds that require manual harvesting. As a result, its floral bud duration, determined by the opening time, is a key determinant of both quality and economic value. However, the genetic mechanisms controlling floral bud duration remain poorly understood. In this study, we employed population structure analysis and molecular experiments to identify candidate genes associated with this trait. The improved cultivar Beihua No. 1 (BH1) opens its floral buds significantly later than the landrace Damaohua (DMH). Exogenous application of methyl jasmonate (MeJA) to BH1 indicated that jasmonate acts as a negative regulator of floral bud duration by accelerating floral bud opening. A genome-wide selection scan across 35 germplasms with varying floral bud durations identified the transcription factor LjWRKY50 as the causative gene influencing this trait. The dual-luciferase reporter assay and qRT-PCR experiments showed that LjWRKY50 activates the expression of the jasmonate biosynthesis gene, LjAOS. A functional variant within LjWRKY50 (Chr7:24636061) was further developed into a derived cleaved amplified polymorphic sequence (dCAPS) marker. These findings provide valuable insights into the jasmonate-mediated regulation of floral bud duration, offering genetic and marker resources for molecular breeding in L. japonica.